Whistleblowing of bullying in professional football: To report or not to report?. (July 2022) - Newman, James A.; Warburton, Victoria E.; Russell, Kate
Abstract: Only recently has research begun to focus on workplace bullying within organizations outside of traditional white-collar industries, such as professional football. While this is an important development, there remains a lack of understanding around the reporting of bullying in professional sport. In this paper, the authors explore how the professional football workplace shapes perceptions of whistleblowing and unearths individual perceptions around reporting bullying behavior. We used a phenomenological approach to gain rich experiential data from eighteen male professional football players in the UK. Interview data were analyzed in accordance with the principles of Interpretative Phenomenological Analysis. Two superordinate themes were identified from the analysis, (a) professional football's influence on whistleblowing, and (b) the challenges of reporting bullying. These themes highlighted that the unique, institutionalized nature of professional football interacts with participants' ability to report bullying behavior. The participants' accounts revealed divergent perceptions around how professional football shapes the degree to which players feel they can report bullying behavior. It was apparent that the authoritarian, often abusive and intimidatory nature of professional football significantly impacts whistleblowing. Our findings demonstrate the importance of workplace context when exploring the reporting of bullying behavior. They also demonstrate the need to address organizational culture and differentiate bullying education programs to alternative workplaces. Highlights: This study explores whistleblowing in the unique context of professional football. Professional football as a workplace influences the degree to which bullying can be reported. Reporting bullying in professional football is especially challenging compared to other workplaces. The professional football context and its organizations interact with an individual's ability to report bullying. Education programs need to address the institutionalized culture of football's organizations.